Recyclable aminophenylboronic acid modified bacterial cellulose microspheres for tetracycline removal: Kinetic, equilibrium and adsorption performance studies for hoggery sewer. (15th August 2022) - Zhang, Gengrong; Li, Linhan; Zhou, Guoqing; Lin, Zhiyang; Wang, Jun; Wang, Gaoxue; Ling, Fei; Liu, Tianqiang
Abstract: Significant concerns have been raised regarding to the pollution of antibiotics in recent years due to the abuse of antibiotics and their high detection rate in water. Herein, a novel super adsorbent, boronic acid-modified bacterial cellulose microspheres with a size of 415 μm in diameter was prepared through a facile water-in-oil emulsion method. The adsorbent was characterized by atomic force microscopy, scanning electron microscopy, and fourier transform infrared spectroscopy analyses to confirm its properties. The microspheres were applied as packing materials for the adsorption of tetracycline (TC) from an aqueous solution and hoggery sewer via the reversible covalent interaction between cis-diol groups in TC molecules and the boronic acid ligand. TC adsorption performance had been systemically investigated under various conditions, including the pH, temperature, TC concentration, contact time, and ionic strength. Results showed that the adsorption met pseudo-second-order, Elovich kinetic model and Sips, Redlich-Peterson isothermal models. And the adsorption process was spontaneous and endothermic, with the maximum TC adsorption capacity of 614.2 mg/g. After 18 adsorption-desorption cycles, the adsorption capacity remained as high as 84.5% compared with their original adsorption capacity. Compared with other reported adsorption materials, the microspheres had high adsorption capacity, a simple preparation process, and excellent recovery performance, demonstrating great potential in application on TC removal for water purification and providing new insights into the antibiotic's adsorption behavior of bacterial cellulose-based microspheres. Graphical abstract: Image 1 Highlights: Boronic acid modified bacterial cellulose microspheres were prepared via emulsion. The microspheres of 415 μm in diameter were characterized by SEM, AFM, IR and TGA. Tetracycline adsorption capacities on the microspheres were 614.2 mg/g. The microspheres could be recycled for 18 cycles with 84.5% adsorption recovery. The recyclable microspheres had good adsorption for real hoggery sewer samples.